Estrategias didácticas a través del método doman para la estimulación del lenguaje oral en niños y niñas de 4 a 5 años de la unidad educativa “Verbo Divino”. - Domínguez Paredes., Carla Elizabeth (2023)
The purpose of this project is to contribute with methodological strategies based on Glen Doman’s reading or intelligence bits, as its creator says, these are for children to learn to read at an early age since their brains have more neural connections from there. performs, all this knowledge has helped me to base myself on the bits as a strategy for the stimulation of oral language in children who attend Initial II sub level 4 years of the Divine Verb Educational Unit. The application was made for a space of class hours for study and application of the proposal called EL CAMPAMENTO DE LAS PALABRAS “Veo y prendo”, from a study based on children and teachers. The method used is of a qualitative type, working with 3 research groups, of which a control group was formed in which the observation sheet was applied prior to the application of the proposal and the other group was experimental, to whom I apply the proposal. The study collected information through three tools, the first was designed to find out what degree of knowledge teachers have about the Doman method, the second was an observation sheet to observe the development of children’s oral language, and the third was the observation sheet, but this time it was to evaluate the children’s language after applying the proposal. These results were evaluated and statistically contrasted through the application of SPSS, which allowed contrasting the data with a significance level greater than 95%, thus confirming that the application of the reading bits proposed in the Doman method help to stimulate, strengthen the oral language of boys and girls.